Guided Navigation Control of an Unmanned Ground Vehicle using Global Positioning Systems and Inertial Navigation Systems - Pooja Velaskar; Alvaro Vargas-Clara; Osama Jameel; Sangram Redkar (Institute of Advanced Engineering and Science, 2014)
This paper demonstrates the use of Global Positioning System (GPS) and Inertial Navigation System (INS) in order to develop an Unmanned Ground Vehicle (UGV) devised to perform a wide variety of outdoor tasks. There are many applications for autonomous UGVs such as tactical and surveillance applications, exploration of areas inaccessible by humans. Capable to navigate to a specific location, and control their motion depending on their surroundings without human intervention. The inertial navigation system makes use of Inertial Measurement Units (IMUs) to measure the change to the UGV's positional parameters, orientation and speed which are continuously monitored and updated. With the advent of GPS, and the positional data from the inertial system the positional information is computed leading to a more accurate control of the UGV; which otherwise suffers from integration drift that occurs with the implementation of inertial systems alone. Autonomous control of the UGV is implemented by coupling GPS sensor and Mission Planner, a tool to map waypoints from Google Maps. Furthermore, system stability and ideal PID (Proportional, Integral and Derivative) values are determined using bicycle modeling analysis to achieve better estimates and control of the UGV.DOI:http://dx.doi.org/10.11591/ijece.v4i3.5183